2018
DOI: 10.5194/acp-18-11581-2018
|View full text |Cite
|
Sign up to set email alerts
|

Production of N<sub>2</sub>O<sub>5</sub> and ClNO<sub>2</sub> in summer in urban Beijing, China

Abstract: Abstract. The heterogeneous hydrolysis of dinitrogen pentoxide (N 2 O 5 ) has a significant impact on both nocturnal particulate nitrate formation and photochemistry on the following day through the photolysis of nitryl chloride (ClNO 2 ), yet these processes in highly polluted urban areas remain poorly understood. Here we present measurements of gas-phase Further analysis indicates that the fast N 2 O 5 loss in the nocturnal boundary layer in urban Beijing is mainly attributed to its indirect loss via NO 3 , … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 88 publications
2
28
2
Order By: Relevance
“…Significant production of ClNO 2 , in addition to N 2 O 5 uptake, was observed, indicating that saline mineral dust particles could be an important source for chlorine species (e.g., ClNO 2 ) in continental North America (Mitroo et al, 2019). Our present work showed that the amounts of chloride could be substantial for saline mineral dust particles collected in northern China, where high levels of N 2 O 5 up to several parts per billion by volume were observed Wang et al, 2018;Zhou et al, 2018). Therefore, heterogeneous reactions of saline mineral dust particles can be an important source for the observed ClNO 2 in north China.…”
Section: Atmospheric Implications 341 Implications For Heterogeneosupporting
confidence: 54%
“…Significant production of ClNO 2 , in addition to N 2 O 5 uptake, was observed, indicating that saline mineral dust particles could be an important source for chlorine species (e.g., ClNO 2 ) in continental North America (Mitroo et al, 2019). Our present work showed that the amounts of chloride could be substantial for saline mineral dust particles collected in northern China, where high levels of N 2 O 5 up to several parts per billion by volume were observed Wang et al, 2018;Zhou et al, 2018). Therefore, heterogeneous reactions of saline mineral dust particles can be an important source for the observed ClNO 2 in north China.…”
Section: Atmospheric Implications 341 Implications For Heterogeneosupporting
confidence: 54%
“…The release of HCl through acid displacement leads to a deficit in particulate Cl − concentrations which can be expressed in terms of a chloride depletion factor (Eq. 12), where Na + and Cl − represent the concentrations in moles per cubic metre and 1.174 is the molar ratio of Cl − to Na + found in seawater (Zhuang et al, 1999).…”
Section: Atom Generation From Clno 2 and Hclmentioning
confidence: 99%
“…As a result of the significance of HONO to tropospheric photochemistry, accurate and precise concentration measurements are required but are challenging due to a number of known potential artefacts in the available approaches. Positive artefacts can occur in inlet lines, as HONO is easily formed through heterogeneous reactions on wet surfaces (Zhou et al, 2002). Furthermore, the highly reactive nature of HONO means that within inlet lines, wall interactions could also lead to a negative artefact unless inert materials are employed (Pinto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%